Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T18:41:48+01:00
A) (2x-3)-(x+5)+(x+4) = 2x-3-x-5+x+4 = 2x-4
b) (3a-2)-(a+4)+(a-3) = 3a-2-a-4+a-3 = 3a-9
c) 4(2y-7y do drugiej)-3(y do drugiej-3y) = 8y-28y²-3y²+9y = -31y²+17y
d) -5(2b+3z)+2(2b-4z) = -10b-15z+4b-8z = -6b-23z
3 3 3
2010-02-02T18:44:54+01:00
(2x-3)-(x+5)+(x+4)=2x-3+x-5+x+4= 6 +4x
(3a-2)-(a+4)+(a-3)= 3a - 2 +a - 4 +a -3= 5a-9
4(2y-7y do drugiej)-3(y do drugiej-3y)= 8y-28y²-3y²+9y= 17y - 31y²
-5(2b+3z)+2(2b-4z) = -10b -15z +4b-8z= -6b -23z

2010-02-02T18:46:33+01:00
A)(2x-3)-(x+5)+(x+4)=2x-3-x-5+x+4=2x-4
b)(3a-2)-(a+4)+(a-3)=3a-2-a-4+a-3=3a-9
c)4(2y-7y do drugiej)-3(y do drugiej-3y)=8y-28y do drugiej - 3y do drugiej + 9y=17y-31y do drugie
d)-5(2b+3z)+2(2b-4z)=-10b-15z+4b-8z=-6b-23z